Workplace toxicity: exploring the impact of toxic work relationships among employees - Siow, Zi Hao (2024)
The goal of this study is to establish a better understanding of the characteristics of toxic colleagues, the negative consequences of having to work with toxic colleagues, and the potential solutions to toxic colleagues in Malaysia. Qualitative data was gathered from 14 Malaysian employees through interviews and was analyzed through template analysis. The findings indicated that, from the perspectives of Malaysian employees, the characteristics of toxic colleagues consist of ostracism, incivility, narcissism, and manipulative. Job burnout is found to be the negative consequence experienced by Malaysian employees for working alongside toxic colleagues. The potential solutions for the company in addressing toxic colleagues suggested by Malaysian employees are the incorporation of a toxic handler, a training regime that emphasizes more on interpersonal skills, and a strengthened hiring screening mechanism. The implications of this study point toward a need for a better awareness of toxic colleagues and their negative consequences from both companies and employees. More importantly and in tandem with the Conservation of Resources theory, team bonding initiatives should be considered and carried out by all companies to help all employees realize the work relationships that they share with one another as important resources.